Influence Of Group Dynamics Factors On Technology Transfer Effectiveness Among Members And Non-Members Of Soybean Grower Groups In Chiangmai, Thailand - Waraegsiri, Boonsam (1995)
The purpose of this study was to determine whether or not the group dynamics factors adapted from selected group behaviour models influence the technology transfer effectiveness (TTE) of the soybean grower group (SOG) farmers and non-soybean grower group (non-SOG) farmers. The correlational study employed the survey research methodology. The data collection tools included personal interview and self-administered questionnaire. A multi-stage random sampling technique was used to select 200 soybean farmers from 24 villages and 24 extension agents within Chiangmai province. Descriptive and inferential statistics (frequency, t-test, Pearson's correlation, multiple regression, and discriminant analysis) were used to analyse the data. The study revealed that the technology transfer effectiveness (TTE) in both SGG members and non-SOG members was high. In comparison, the SOG members' TTE was significantly higher than the non-SOG members.